Just a FAD? Ecosystem impacts of tuna purse‐seine fishing associated with fish aggregating devices in the western Pacific Warm Pool Province. (17th September 2018) - Griffiths, Shane P.; Allain, Valerie; Hoyle, Simon D.; Lawson, Tim A.; Nicol, Simon J.
Abstract: The western and central Pacific Ocean supports the world's largest tuna fisheries. Since the 1990s, the purse‐seine fishery has increasingly fished in association with fish aggregating devices (FADs), which has increased catches of juvenile bigeye and yellowfin tunas and vulnerable bycatch species (e.g., sharks). This has raised concerns regarding the sustainability of these species' populations and the supporting ecosystem, but may provide improved food security of Pacific Island nations through utilisation of FAD‐associated byproduct species (e.g., wahoo). An ecosystem model of the western Pacific Warm Pool Province was used to explore the potential ecological impacts of varying FAD fishing effort (±50% or 100%) over 30 years. The ecosystem has undergone a significant change in structure since 1980 from heavy exploitation of top predators (e.g., tunas) and "fishing up the food web" of high‐trophic‐level non‐target species. The ecosystem appeared resistant to simulated fishing perturbations, with only modest changes (<10%) in the biomass of most groups, although some less productive shark bycatch species decreased by up to 43%, which had a subsequent positive effect on several byproduct species, the prey of sharks. Reduction of FAD effort by at least 50% was predicted to increase the biomass of tuna species and sharks and return the ecosystem structure to a pre‐industrial‐fishing state within 10 years. Spatial disaggregation of the model and integration of economic information are recommended to better capture ecological and economic changes that may result from fishing and/or climate impacts and to develop appropriate management measures in response.